Iudei et ceteri …: Bemerkungen zur rechtlichen, sozialen und wirtschaftlichen Stellung der Juden in karolingischer und ottonischer Zeit - Wenninger, Markus J. (Aschkenas, 2020)
This study analyzes the formulation »Jews and (other) merchants« as it appears in sources from the 9th to the early 11th centuries. It addresses Michael Toch’s thesis with an aim to clarify the historical meaning of such formulations. By doing so, this study sheds light on how specific social differences between Jewish and non-Jewish merchants arose, while economic activities among both groups remained the same. Both Jews and non-Jews traded in the whole Frankish Empire and beyond. Both groups, therefore, took part in the lucrative as well as extensive slave trade, which was an essential element of the long-distance trading of the early Middle Ages.